Arsenic resistance and accumulation by two bacteria isolated from a natural arsenic contaminated site. (19th June 2015) - Pandey, Neha; Bhatt, Renu
<x xml:space="preserve">Abstract</x> Forty‐three indigenous arsenic resistant bacteria were isolated from arsenic rich soil of Rajnandgaon district in the state of Chhattisgarh, India by enrichment culture technique. Among the isolates, two of the bacteria (As‐9 and As‐14) exhibited high resistance to As(V) [MIC ≥ 700 mM] and As(III) [MIC ≥ 10 mM] and were selected for further studies. Both these bacteria grew well in the presence of arsenic [20 mM As(V) and 5 mM As(III)], but the isolate As‐14 strictly required arsenic for its survival and growth and was characterized as a novel arsenic dependent bacterium. The isolates contributed to 99% removal of arsenic from the growth medium which was efficiently accumulated in the cell. Quantitative estimation of arsenic through Atomic Absorption Spectrophotometer revealed that there was >60% accumulation of both As(V) and As(III) by the two isolates. Scanning Electron Microscopic analysis showed a fourfold increase in bacterial cell volume when grown in the presence of arsenic and the results of Transmission Electron Microscopy and energy‐dispersive X‐ray spectroscopy proved that such an alteration was due to arsenic accumulation. Such arsenic resistant bacteria with efficient accumulating property could be effectively applied in the treatment of arsenic contaminated water.